2021
DOI: 10.3390/jcm10020321
|View full text |Cite
|
Sign up to set email alerts
|

Edema Resolution and Clinical Assessment in Poor-Grade Subarachnoid Hemorrhage: Useful Indicators to Predict Delayed Cerebral Infarctions?

Abstract: Background: The level of consciousness and cerebral edema are among the indicators that best define the intensity of early brain injury following aneurysmal subarachnoid hemorrhage (aSAH). Although these indicators are usually altered in patients with a poor neurological status, their usefulness for selecting patients at risk of cerebral infarction (CI) is not well established. Furthermore, little is known about the evolution of these indicators during the first week of post-ictal events. Our study focused on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…246,251,[255][256][257] The duration of frequent assessments also varied, with a range of at least 48 hours to 7 days after the bleed. 245,246,[254][255][256][257] One study observed neurological deterioration in 42.6% of patients after aneurysm clipping using the GCS and NIHSS as the frequent assessment tool every hour up to 72 hours. 256 There are a lack of consensus and wide variability in the timing and duration of frequent assessments, allowing more individualized care plans based on the complexity and needs of the patient.…”
Section: Early Detection Of Neurological Deterioration Formentioning
confidence: 99%
See 3 more Smart Citations
“…246,251,[255][256][257] The duration of frequent assessments also varied, with a range of at least 48 hours to 7 days after the bleed. 245,246,[254][255][256][257] One study observed neurological deterioration in 42.6% of patients after aneurysm clipping using the GCS and NIHSS as the frequent assessment tool every hour up to 72 hours. 256 There are a lack of consensus and wide variability in the timing and duration of frequent assessments, allowing more individualized care plans based on the complexity and needs of the patient.…”
Section: Early Detection Of Neurological Deterioration Formentioning
confidence: 99%
“…The studies reviewed include both RCTs and non-RCTs with a consistent recommendation for nurses to provide frequent assessments in the acute phase. [244][245][246][254][255][256][257] Frequent assessments ranged from every 15 minutes to every 4 hours. 246,251,[255][256][257] The duration of frequent assessments also varied, with a range of at least 48 hours to 7 days after the bleed.…”
Section: Early Detection Of Neurological Deterioration Formentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier detection and intensive monitoring are only the initial steps in the paradigm shift that is needed for treatment to prevent poor outcomes following aSAH [ 49 ]. Adequate EVT is also necessary with a variety of treatment options, ranging from balloon angioplasty [ 19 , 20 , 21 , 22 , 23 , 24 ] and stentoplasty [ 25 , 26 , 27 , 28 , 29 ] to IA medicinal vessel dilatation, in addition to combined approaches.…”
Section: Discussionmentioning
confidence: 99%